Tingkat Pengetahuan tentang Persiapan Kehamilan pada Remaja Putri di SMA Negeri 1 Sedayu Bantul Yogyakarta - Siti Nurunniyah; Mulyanti Mulyanti; Rita Nur Octafiyani (Alma Ata University Press, 2014)
Pregnancy preparation has to be undertaken since women in teenage. The risk of anemia, KEK, and neglegance of pregnancy causes by poor knowledge. This is a descriptive quantitative research using crosssectional design. It was 118 of Sedayu I public high schools student participating in the research determined bystratiﬁed random sampling technique. Questioner of pregnancy preparation used as tool to collect data. Univariate analysis presents that degree of knowledge of preganancy preparation on teen students was average ((56%/66 repondents). Indicators of degree of knowledge include deﬁnition in good category (100%);understanding of ideal health reproduction in average (66%/78 respondents); tetanus toxoid immunization in lower category (72%/85 people);understanding of folic acid in average category (57%/67 people);anemia in great category by 85 respondents (72%); and diet status in average category (49%/58 people). Conclusion, the level of knowledge of teen women students on the pregnancy preparation is mostly in good level, while, understanding of tetanus toxoid immunication is low.